Impact of Electric Vehicle Charging Station on Harmonics and Voltage Stability of Grid System using MATLAB Simulink - Ruzlan, Nor Izzah Nadhirah; Mohd Noor Abdullah, (Evolution in Electrical and Electronic Engineering, 2024)
The minimal to virtually negligible environmental footprint associated with electric vehicles (EVs) has generated considerable interest among researchers, sparking extensive and ongoing investigations. The focus of this research pertains to the charging infrastructure, with active exploration of fast chargers, wireless charging technologies, and various methodologies aimed at expediting the charging process. The proliferation of EVs poses a significant challenge to the harmonic and voltage stability of grid systems. As the adoption of EVs increases, the dynamic and non-linear nature of their charging and discharging processes introduces potential disturbances to the grid, leading to harmonic distortions and voltage fluctuations. In this paper, the impact of electric vehicle charging stations on grid system is analyzed in terms of harmonics and voltage stability. The results derived from Simulink for THD values increase when increase EV from 1 to 4 EV. For 1 EV, THD values 14.9% then for 4 EV, the THD values 27.2%. The harmonic pollution associated with EVs dependent on the number of EVs and the charging method. If many EVs are charging in the same area, then the harmonic pollution in that area will be more. The simulation study of DC fast charging using Simulink in MATLAB has provided valuable insights into the impact of EVs charging stations on the grid system, with a specific focus on voltage stability and harmonic distortion.